Is the broadcast WhatsApp group still effective for delivering emergency messages to Gen Z? - Widodo, Suko (Jurnal Komunikasi Profesional, 2025)
This study examines the effectiveness of WhatsApp broadcast groups as a channel for delivering emergency messages to Generation Z (Gen Z) in Indonesia, a demographic heavily reliant on digital platforms amid rising platform fragmentation. The study advocates hybrid strategies integrating WhatsApp with multi-platform, interactive tools to optimizee research qualitatively evaluates four core dimensions: reach, timeliness, clarity, and interactivity of broadcasted alerts. FGD participants highlight WhatsApp's advantages, including near-universal adoption, high open rates, and rapid delivery, positioning it as a reliable first-alert mechanism during crises like natural disasters or public health emergencies prevalent in Indonesia. Nonetheless, limitations emerge prominently: one-way messaging fosters overload from group saturation, diminishes engagement compared to interactive TikTok or Instagram formats, and encounters selective exposure influenced by Gen Z's disaster information literacy and preference for multimedia-rich updates. Findings reveal that while broadcast groups retain conditional viability, their standalone efficacy wanes against Gen Z's demand for personalized, bidirectional communication. The study advocates hybrid strategies integrating WhatsApp with multi-platform, interactive tools to optimize emergency reach and response among this cohort.